Neandertal versus Modern Human Dietary Responses to Climatic Fluctuations - El Zaatari, Sireen (PLoS One, 2016)
The Neandertal lineage developed successfully throughout western Eurasia and effectively survived the harsh and severely changing environments of the alternating glacial/interglacial cycles from the middle of the Pleistocene until Marine Isotope Stage 3. Yet, towards the end of this stage, at the time of deteriorating climatic conditions that eventually led to the Last Glacial Maximum, and soon after modern humans entered western Eurasia, the Neandertals disappeared. Western Eurasia was by then exclusively occupied by modern humans. We use occlusal molar microwear texture analysis to examine aspects of diet in western Eurasian Paleolithic hominins in relation to fluctuations in food supplies that resulted from the oscillating climatic conditions of the Pleistocene. There is demonstrable evidence for differences in behavior that distinguish Upper Paleolithic humans from members of the Neandertal lineage. Specifically, whereas the Neandertals altered their diets in response to changing paleoecological conditions, the diets of Upper Paleolithic humans seem to have been less affected by slight changes in vegetation/climatic conditions but were linked to changes in their technological complexes. The results of this study also indicate differences in resource exploitation strategies between these two hominin groups. We argue that these differences in subsistence strategies, if they had already been established at the time of the first contact between these two hominin taxa, may have given modern humans an advantage over the Neandertals, and may have contributed to the persistence of our species despite habitat-related changes in food availabilities associated with climate fluctuations.